The Impact of International Remittances on Financial Development in Nigeria: 1981-2021 - Mustapha-Jaji, Olaide Kafayat; Adesina-Uthman, Ganiyat A. (Acta Universitatis Danubius. Œconomica, 2023)
Interconnectivity between international remittances and financial development has been center of academic discussions in recent time. High cost of remittances and underdeveloped financial system may be counterproductive as remittances may flow more through informal avenues than formal ones. Consequently, its impact on financial development may not be adequately captured. This study examined the impact of remittances on financial development in Nigeria for the period 1981 to 2021. The study measured financial development by banking sector development and stock market development, and analyzed the data using the auto-regressive distributed lag estimation techniques. The findings of the study showed that international remittances had positive and significant impact on banking sector development while international remittance had insignificant impact on stock market development. Thus, the study concluded that international remittances had different impact on measures of financial sector development. Hence, the study recommends among others the need for government to ensure that the high cost of remittances is reduced, such that significant percentage of the remittances can be kept in the financial system through innovative banking products.